A CHECK-LIST OF EARLY BOOKKEEPING TEXTS. - Hatfield, H. R.; Littleton, A. C. (The Accounting Review, 1932)
The article presents a list of books regarding accounting, published in the September 1932 issue of the journal "The Accounting Review." Some of the books are: "Book-Keeping," by Daniel Adams, "Key to Book-Keeping," by Israel Alger, "The Young Accountant's Guide," by Frederick Beck, "The National Accountant," by Jacob Batchelder, "A Synthetic and Inductive System of Book-Keeping by Double Entry," by F.G. Clarke, "Modern Book-Keeping by double entry," by Charles Gerisher, "A new and Improved System of Practical Book-Keeping," by John Gibson, "A System of Banking Book-Keeping," by J.W. Gilbert, "An Epitome of Book-Keeping by Double Entry," by Edmund Gale, "The Gentleman's Complete Book-Keeping," by Richard Hayes, "New Introduction to Trade and Business," by Peter Hudson, "The Schoolmaster's Guide," by Charles Hutton, "A Practical Treatise on Naval Book-Keeping," by Edward Lawes, "Book-Keeping in the True Italian Form of Debtor and Creditor by Way of Double Entry," by William Jackson and "A New Check Journal Upon the Principle of Double Entry," by George Jackson, etc.